2019
DOI: 10.1002/pssa.201800877
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress in Understanding the Properties of the Amorphous Silicon/Crystalline Silicon Interface

Abstract: The authors review experimental and modeling approaches developed at GeePs to have a better knowledge and understanding of the interface between hydrogenated amorphous silicon (a‐Si:H) and crystalline silicon (c‐Si) in heterojunction solar cells. The authors emphasize the existence of a strong inversion layer at the c‐Si surface for both (n) a‐Si:H/(p) c‐Si and (p) a‐Si:H/(n) c‐Si heterojunctions. Conductive probe atomic force microscopy reveals the existence of a conductive channel at the c‐Si surface. The an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 75 publications
(88 reference statements)
0
3
0
Order By: Relevance
“…Data from Ref. [30]. Figure 2 illustrates the topography and the local resistance mapping on the cross-section after a HF dip and for an applied voltage of 1 Volt.…”
Section: C-afm Investigation Of A-si:h/c-si Interfacementioning
confidence: 99%
“…Data from Ref. [30]. Figure 2 illustrates the topography and the local resistance mapping on the cross-section after a HF dip and for an applied voltage of 1 Volt.…”
Section: C-afm Investigation Of A-si:h/c-si Interfacementioning
confidence: 99%
“…www.advancedsciencenews.com www.pss-rapid.com decreases below 10 nm was also suggested from the modeling of the effective lifetime in these structures, assuming that interface defects responsible for recombination of carriers photogenerated in c-Si can be considered as an extension of the DOS in (i) a-Si:H. [36] In conclusion, we have shown that the static planar conductance of (p) a-Si:H/(i) a-Si:H/(n) c-Si structures is very useful as it does not depend on recombination parameters like capture cross-sections, and it allows one to obtain a clear picture of the band bending at the heterojunction. A detailed analysis from both 1D analytical and 2D full numerical calculations was used to determine the evolution of the deep defect density N DB in (i) a-Si:H as a function of the layer thickness.…”
mentioning
confidence: 96%
“…Conversely, for the thicker (i) a‐Si:H layer of 50 nm, the value of the valence band tail width cannot be larger than 50 meV, meaning that with such thickness, the deposited material is equivalent to that of the device grade–thick “bulk” material . It is worth mentioning that an increase in the valence band tail width when the (i) a‐Si:H thickness decreases below 10 nm was also suggested from the modeling of the effective lifetime in these structures, assuming that interface defects responsible for recombination of carriers photogenerated in c‐Si can be considered as an extension of the DOS in (i) a‐Si:H …”
mentioning
confidence: 99%